Physiological Responses and Adaptations of the Halophyte Atriplex halimus to Soil Contaminated with Cd, Ni, and NaCl - Shumailah Ishtiyaq; Harsh Kumar; Rohan J. D’Souza; Mayank Varun; Paulo J. C. Favas; Manoj S. Paul (Soil Systems, 2023)
Soils contaminated with potentially toxic elements (PTEs) and salt manifest a large number of physical, chemical, and structural problems by various processes such as reduced water availability, water and air movement in soil space, water holding capacity of soil, as well as perilous effects on plant growth and physiology. Halophytes have the ability to grow in saline environments and are better adapted to accommodate environmental constraints including PTE ions. An experiment was designed to study the response of the halophyte Atriplex halimus to a range of salinities and different concentrations of Cd and Ni. Tolerance and soil remedial potential of the plant were quantified in terms of PTE uptake and portioning, plant biomass, root/shoot ratio, chlorophyll and anti-oxidative enzyme production, along with stress markers such as lipid peroxidation, proline, and glycine betaine. The plant was also evaluated for its potential to phytoremediate PTE contaminated soil. The results suggest that A. halimus can tolerate moderate concentrations of both the PTEs and salt. The species holds promise for bio-reclamation of saline and PTE-contaminated soil.